The Histological Structures of Tail Bones in Ovariectomi and Non-ovariectomi Rats - Dian Masyitha (Jurnal Medika Veterinaria, 2014)
This experiment was conducted to study the microscopic structure of tail bones in ovariectomized and non-ovariectomy rats. Fourteen femaleSprague Dawley rats 7 weeks old were randomly divided into 2 groups. The rats in the control group were non-ovariectimized. The rats in groupII were ovariectomized. The samples were then fed with phosphate/calcium diet with ratio of 2 to 1. The rats was sacrificed after 12 weeks. Thetail bone were collected and processed for microscopic examination with trichrome staining. The results showed that structurally theosteoporosis occurred in tail bone of group K2. Its could be concluded that estrogen deficiency condition (ovariectomy) caused osteoporosis intail bones.____________________________________________________________________________________________________________________Key words: osteoporosis, ovariectomy, tail bone